Knowledge of Hyperemic Myocardial Blood Flow in Healthy Subjects Helps Identify Myocardial Ischemia in Patients With Coronary Artery Disease - Lyu, Lijuan; Pan, Jichen; Li, Dumin; Li, Xinhao; Yang, Wei; Dong, Mei; Guo, Chenghu; Lin, Peixin; Han, Yeming; Liang, Yongfeng; Sun, Junyan; Yu, Dexin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: Dynamic CT myocardial perfusion imaging (CT-MPI) allows absolute quantification of myocardial blood flow (MBF). Although appealing, CT-MPI has not yet been widely applied in clinical practice, partly due to our relatively limited knowledge of CT-MPI. Knowledge of distribution and variability of MBF in healthy subjects helps in recognition of physiological and pathological states. Objectives: To describe the distribution of hyperemic MBF in healthy subjects obtained by dynamic stress CT myocardial perfusion imaging (CT-MPI) and validate whether it can accurately identify functional myocardial ischemia when the cut-off value of hyperemia MBF is set to the lower limit of the normal range. Materials and Methods: Fifty-one healthy volunteers (age, 38 ± 12 years; 15 men) were recruited. One hundred ninety-eight vessels (with 67 vessels diagnosed as ischemic lesions by ICA/ FFR) from 80 patients (age, 58 ± 10 years; 55 men) with suspected or known coronary artery disease (CAD) who completed both CT-MPI and ICA/FFR examinations were retrospectively recruited. ICA/FFR was used as the reference standard for diagnosing functional ischemia. The normal range for the hyperemic MBF were defined as the mean ±1.96 SD. The cut-off value of hyperemic MBF was set to the lower limit of the normal range. Results: The global hyperemic MBF were 164 ± 24 ml/100 ml/min and 123 ± 26 ml/100 ml/min for healthy participants and patients. The normal range of the hyperemic MBF was 116-211 ml/100 ml/min. In the per-vessel analysis, an MBF cutoff value of less than 116 ml/100 ml/min can identify myocardial ischemia with a diagnostic accuracy, sensitivity, specificity, PPV, and NPV of 85.9% (170/198), 91.0 % (61/67), 83.2 % (109/131), 73.5% (61/83), and 94.8% (109/115). CT-MPI showed good consistency with ICA/FFR in diagnosing functional ischemia, with a Cohen’s kappa statistic of 0.7016 (95%CI, 0.6009 - 8023). Conclusion: Recognizing hyperemic MBF in healthy subjects helps better understand myocardial ischemia in CAD patients.